PENGARUH KOMPETENSI PADA KINERJA AUDITOR INTERNAL DENGAN MOTIVASI, KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI PEMODERASI DI INSPEKTORAT KABUPATEN TABANAN - Ary Indrayanti, Sagung Mas; Suprasto, Herkulanus Bambang; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aimed to get empirical evidence about the effect of competence on the performance the internal auditor with Motivation, Organizational  Commitment and Environmental Uncertainty as moderating in Tabanan District Inspectorate. Inspectorate research location in Tabanan regency. The research sample was determined by the census technique. Data collected by the survey technique in the form of questionnaire and interview to 45 an internal auditor at the Inspectorate. Data analysis technique used is Moderated Regression Analysis (MRA). The results showed that : (1) Motivation strengthen competence influence on performance; (2) Commitment to the organization does not strengthen the competence influence on performance; (3) strengthening the influence of environmental uncertainty competency in performance.
Keywords: : Performance, Competence, Motivation, Organizational Commitment and Environmental Uncertainty